HYDROPROCESSING OF DIZEL OIL FRACTIONS ON MODIFIED ALUMINA CATALYSTS - Tuktin BalgaTuctievich; Tenizbayeva Aliya Serikovna; Shamshat Nurbek Auesbayuly; Abilmagjanov Arlan Zanutallaevich; Shapovalov Anatoly Aleksandrovich (Academic Scientific Journal of Chemistry, 2019)
The paper presents the results of a study of hydroforming diesel oil fractions on alumina catalysts modified with metals of variable valency, the addition of phosphorus and lanthanum. The study of the process of hydroprocessing of the diesel fractions was carried out in a high-pressure flow unit with a stationary catalyst bed at temperature of 320-4000 C, a pressure of 3 - 4.0 MPa and a volume feed rate of 1-3 h-1. The results obtained during the tests of catalysts in the process of hydroprocessing of diesel oil fractions show that the greatest decrease in the pour point and turbidity occurs at a temperature of 380–400o C. During the hydroprocessing of the diesel fraction, the lowest residual sulfur content is observed at a temperature of 400o C. During the hydroprocessing of the diesel fractions of oil, the catalyst СоО-WO3- La2О3 - Р2О5-ZSM- Al2O3, has the greatest hydrodesulfurizing activity. The sulfur content of the catalysate with increasing temperature up to 400o С decreased from 0,560 to 0,0229%. The greatest decrease in the pourpoint and сloudpoint, during the hydroprocessing of the diesel oil fraction is observed on the catalyst NiO-МоO3-La2О3-Р2О5-ZSM-Al2O3: minus 58.9 and minus 57.7o C, respectively. Physical and chemical characteristics of catalysts are studied. The method of temperature–programmed desorption of ammonia found that the highest concentration of acid centers has a catalyst NiO-МоO3-La2О3-Р2О5- ZSM-Al2O3 (31.3•10-4mol NH3des /g cat) with Tdes= 2150 C, which determines its high hydroisomerizing activity in the processes of hydroprocessing of diesel fractions. The developed catalysts make it possible to obtain winter grades of diesel fuels with low sulfur content.